Next-Generation-Sequencing-Based Simple Sequence Repeat (SSR) Marker Development and Linkage Mapping in Lentil (Lens culinaris L.) - Topu, Mustafa; Sesiz, Ugur; Bektas, Harun; Toklu, Faruk; Ozkan, Hakan (Mdpi, 2023)
Simple Summary Although lentil is not as popular as other legumes, it is a climate-resilient legume crop because of its high protein content, nitrogen fixation, and abiotic stress tolerance ability. Even though it can be grown on almost every continent and is distributed globally, the use of existing genetic diversity in marker-assisted selection is still limited. In this study, novel SSR markers needed in lentil were identified using a next-generation sequencing approach. In this study, we created a ready-to-use SSR library for genetic diversity studies and breeding and evaluated the effectiveness of the obtained SSR markers in a recombinant inbred line (RIL) population. Simple sequence repeats (SSRs) are highly versatile markers in genetic diversity analysis and plant breeding, making them widely applicable. They hold potential in lentil (Lens culinaris) breeding for genetic diversity analysis, marker-assisted selection (MAS), and linkage mapping. However, the availability and diversity of SSR markers in lentil is limited. We used next-generation sequencing (NGS) technology to develop SSR markers in lentil. NGS allowed us to identify regions of the lentil genome that contained SSRs. Illumina Hiseq-2000 sequencing of the lentil genotype Karacadag resulted in 1,727,734 sequence reads comprising more than 48,390 Mb, and contigs were mined for SSRs, resulting in the identification of a total of 8697 SSR motifs. Among these, dinucleotide repeats were the most abundant (53.38%), followed by trinucleotides (30.38%), hexanucleotides (6.96%), tetranucleotides (6.59%), and pentanucleotides (3.19%). The most frequent repeat in dinucleotides was the TC (21.80%), followed by the GA (17.60%). A total of 2000 primer pairs were designed from these motifs, and 458 SSR markers were validated following their amplified PCR products. A linkage map was constructed using these new SSRs with high linkage disequilibrium (209) and previously known SSRs (11). The highest number of SSR markers (43) was obtained in LG2, while the lowest number of SSR markers (19) was obtained in LG7. The longest linkage group (LG) was LG2 (86.84 cM), whereas the shortest linkage group was LG7 (53.46 cM). The average length between markers ranged from 1.86 cM in LG1 to 2.81 cM in LG7, and the map density was 2.16 cM. The developed SSRs and created linkage map may provide useful information and offer a new library for genetic diversity analyses, linkage mapping studies, and lentil breeding programs.
Keywords: lentil; Lens culinaris; SSR development; linkage map; next-generation sequencing